1948
DOI: 10.1002/pol.1948.120030208
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of proteins. IV. Action of ultraviolet light on crystalline chymotrypsin

Abstract: Crystalline chymotrypsin has been inactivated by ultraviolet light (2537 Å.) with a quantum yield of 0.0032 based upon loss of ability to act upon casein as a substrate. The possible significance of this datum in terms of the duo‐specificity of chymotrypsin, the integrity of the molecule as a whole and the quantum efficiency of cleavage of CONH linkages is discussed. The ultraviolet light absorption spectrum of the pure enzyme has been determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1949
1949
1953
1953

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The inactivation of trypsin (269, 277), chymotrypsin (83) and soybean trypsin inhibitor (133) by ultraviolet irradiation has been studied, and the effect of radiant energy on enzymes has recently been reviewed (187). One of the most interesting studies of this type is that of Dale (69), who found that when carboxypeptidase was irradiated with x-rays in the presence of a substrate (the peptic digest of edestin used by Anson), the enzyme was completely protected against a radiation dosage sufficient to cause 85 per cent inactivation in the absence of the substrate.…”
Section: Rosettes Of Needles (159)mentioning
confidence: 99%
See 1 more Smart Citation
“…The inactivation of trypsin (269, 277), chymotrypsin (83) and soybean trypsin inhibitor (133) by ultraviolet irradiation has been studied, and the effect of radiant energy on enzymes has recently been reviewed (187). One of the most interesting studies of this type is that of Dale (69), who found that when carboxypeptidase was irradiated with x-rays in the presence of a substrate (the peptic digest of edestin used by Anson), the enzyme was completely protected against a radiation dosage sufficient to cause 85 per cent inactivation in the absence of the substrate.…”
Section: Rosettes Of Needles (159)mentioning
confidence: 99%
“…The theoretical relation of time and extent of enzymatic hydrolysis to enzyme and substrate concentrations has been considered in a preceding section of this review (page 83). It may not be amiss to consider herein these relations as they pertain to the design of enzymatic experiments.…”
Section: Incubation Time and Extent Of Hydrolysismentioning
confidence: 99%